Rupture of the lateral ventricle secondary to a fourth ventricle tumour resulting in an indirect nontraumatic cerebrospinal fluid fistula - Tan, S.P.; Abdullah, B.J.J.; Waran, V.; Liew, W.F. (2003)
We present a rare indirect nontraumatic cerebrospinal fluid (CSF) fistula secondary to a fourth ventricle ependymoma. The fistula resulted from rupture of the left temporal horn, distant from the tumour. The fistula was well demonstrated by MRI. High-resolution CT demonstrated a defect in the roof of the sphenoid sinus, but no leakage of CSF was seen on CT cisternography.